Effectiveness of hyaluronic acid in post-surgical cures following partial matricectomies with the phenol/alcohol technique: A randomized clinical trial - Lópezosa-Reca, Eva; Martínez-Nova, Alfonso; Sanchez-Rodriguez, Raquel; Gijón-Noguerón, Gabriel; Marchena-Rodríguez, Ana José; Martínez-Rico, Magdalena; Alabau-Dasi, Raquel (Elsevier, 2023)
Background: Post-operative cures with hyaluronic acid (HA) could potentially shorten the period recovery involved in the phenol technique for ingrown toenail. The aim of this study was therefore to compare a standard healing protocol with the experimental one based on hyaluronic acid cream. Material and methods: 70 patients who had undergone phenol technique surgery for ingrown toenail were divided into two groups - control (n = 35) who received post-operative cures following the standard protocol with povidone iodine gel, and experimental (n = 35) who received cures with HA in the first 3 visits. Bleeding, total healing time, and perceived pain were assessed. Results: Patients in the control group recovered from the intervention in a total of 26.17 ± 7.75 days, while those in the HA group recovered in a significantly shorter time - 22.42 ± 2.41 days (p = 0.007, effect size 0.653). However, there were no between-group statistical differences in bleeding or perceived pain over the course of the post-surgery visits. Conclusions: The use of low molecular weight hyaluronic acid is effective in reducing the phenol-technique healing time by 4 days compared with the standard cure. However, no extra effects such as reductions in bleeding or perceived pain can be expected in choosing this healing protocol.
Keywords: Acido hialurónico; Hyaluronic acid; Wound; Post-operative care; Ingrown toenail